Highly sensitive on-chip fluorescence sensor with integrated fully solution processed organic light sources and detectors. Issue 42 (17th May 2017) - Shu, Z.; Kemper, F.; Beckert, E.; Eberhardt, R.; Tünnermann, A.
Abstract : The first reported on-chip fluorescent sensor consisting of fully solution processed organic light sources and detectors. Abstract : We report the first fluorescence light detector combining a fully solution processed organic electrochemical cell (OLEC) and a fully solution processed organic photodiode (OPD) within one microfluidic chip. The blue OLEC was used as the excitation source, whereas the OPD was used for detection of the emitted fluorescent light. Two orthogonally oriented linear polarizers were used as excitation and emission filters, enabling the use of fluorescent dyes with emission and absorption peaks very close to each other. In addition the system is compatible with many different fluorescent dyes. The filters and organic devices were mounted onto a microfluidic glass chip. Fluorescein amidite (FAM) was used as a model dye to characterize and demonstrate the concept of the system. Despite a very close excitation peak (492 nm) and emission peak (518 nm) of FAM, we were able to detect FAM concentrations as low as 1 μM even for a brightness value of the OLEC as low as 500 cd m −2 . This opens the possibility of producing low cost, portable and disposable fluorescence sensors with a high sensitivity.